Laminate and use of the same

A laminate with a 4-methyl-1-pentene polymer resin layer on a glass surface addresses the issues of silicone transfer and lack of heat resistance in existing coating agents, providing excellent water repellency, heat resistance, and residual properties while maintaining glass transparency.

JP2025050233APending Publication Date: 2025-04-04MITSUI CHEMICALS INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023158923
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-22
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing silicone-based coating agents for glass suffer from poor residual properties, as a portion of the silicone in the coating layer transfers to the counter material, contaminating it, and lack heat resistance.

Method used

A laminate is formed on a glass surface using a resin layer composed of a 4-methyl-1-pentene polymer with specific properties, including a melting point between 180°C and 220°C, which provides excellent water repellency, heat resistance, and residual properties while maintaining glass transparency.

Benefits of technology

The laminate achieves excellent water repellency, heat resistance, and residual properties, preventing silicone transfer and maintaining glass transparency, thus addressing the limitations of existing coating agents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025050233000001
    Figure 2025050233000001
  • Figure 2025050233000002
    Figure 2025050233000002
  • Figure 2025050233000003
    Figure 2025050233000003
Patent Text Reader

Abstract

To provide a laminate that maintains transparency of glass, has excellent water repellency and heat resistance, and includes a layer with excellent persistence laminated on a glass surface.SOLUTION: A laminate has: a substrate layer (I) having a surface containing glass; and a resin layer (II) which is formed of a composition (X) containing 4-methyl-1-pentene-based polymer (A) that satisfies the following requirements (a), is in contact with the surface, and has a thickness of 10 μm or less. (a) A melting point (Tm) measured by a differential scanning calorimeter (DSC) exceeds 180°C and 220°C or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate and its use. [Background technology]

[0002] Glass is a material with excellent transparency, and is used in a wide range of applications by taking advantage of its transparency. However, depending on the application, there may be cases where improvement in the water repellency of glass is required. To meet such applications, water repellents for glass have been proposed. For example, Patent Document 1 discloses a silicone-based water repellent for glass that contains an amino-modified polysiloxane having an alkoxy group at the end of the main chain. In addition, Patent Document 2 discloses a silicone-based coating agent for glass in which a silane compound, a dimethylpolysiloxane having a silanol group at both ends of the molecular chain, and a catalyst are diluted with a volatile solvent. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2009-137775 A [Patent Document 2] JP 2016-169307 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, in the coating layer formed using the silicone-based coating agent described in Patent Documents 1 and 2, some of the silicone in the coating layer may migrate to the counter material in contact with the coating surface of the coating agent, contaminating the counter material with silicone. For this reason, there has been a demand for a coating agent that can form a coating layer with excellent residual properties that is less likely to migrate to the counter material in contact with the coating surface. In addition, depending on the application, the heat resistance of the coating layer formed on the glass surface may be required, but Patent Documents 1 and 2 make no mention of the heat resistance of the coating layer.

[0005] An object of the present invention is to provide a laminate in which a layer that maintains the transparency of glass, is excellent in water repellency and heat resistance, and has excellent residual properties, is laminated on the surface of glass. [Means for solving the problem]

[0006] As a result of further investigations, the present inventors have found that the above-mentioned problems can be solved by forming a resin layer (II) made of a composition (X) containing a 4-methyl-1-pentene polymer (A) that satisfies specific requirements on a substrate having a glass surface, and have thus completed the present invention. That is, the present invention has the following features [1] to

[10] .

[0007] [1] A substrate layer (I) having a surface comprising glass; a resin layer (II) having a thickness of 10 μm or less, which is formed from a composition (X) containing a 4-methyl-1-pentene polymer (A) satisfying the following requirement (a) and is in contact with the surface; A laminate having the following structure: (a) The melting point (Tm) measured by differential scanning calorimetry (DSC) is greater than 180°C and less than or equal to 220°C.

[0008] [2] The laminate according to [1], wherein the 4-methyl-1-pentene polymer (A) further satisfies the following requirement (b): (b) The endothermic end temperature (TmE) in the melting (endothermic) curve measured by DSC is 230°C or lower.

[0009] [3] The laminate according to [1] or [2], wherein the 4-methyl-1-pentene polymer (A) further satisfies the following requirement (c): (c) The heat generation onset temperature (TcS) in the crystallization (heat generation) curve measured by DSC is 210°C or lower.

[0010] [4] The laminate according to any one of [1] to [3], wherein the 4-methyl-1-pentene polymer (A) further satisfies the following requirement (f): (f) The crystallization temperature (Tc) in the crystallization (exothermic) curve measured by DSC is 110 to 200°C.

[0011] [5] The laminate according to any one of [1] to [4], wherein the 4-methyl-1-pentene polymer (A) has an intrinsic viscosity [η] measured in decalin at 135° C. in the range of 0.5 to 6.0 dl / g.

[0012] [6] The laminate according to any one of [1] to [5], wherein the amount (U1) of structural units derived from 4-methyl-1-pentene in the 4-methyl-1-pentene polymer (A) is 84.0 to 100.0 mol %, and the total amount (U2) of structural units derived from ethylene or an α-olefin having 3 to 20 carbon atoms (excluding 4-methyl-1-pentene) is 16.0 to 0.0 mol % (the sum of U1 and U2 is 100 mol %).

[0013] [7] The 4-methyl-1-pentene polymer (A) is a graft-modified 4-methyl-1-pentene polymer (A2), The laminate according to any one of [1] to [6], wherein the graft modification amount of the modified 4-methyl-1-pentene polymer (A2) is 0.1 to 5.0% by mass.

[0014] [8] The laminate according to [7], wherein the composition (X) further contains an isocyanate compound (B).

[0015] [9] The substrate layer (I), The resin layer (II), A resin layer (III) having a thickness of 10 μm or less, which is formed from a composition (X1) containing an unmodified 4-methyl-1-pentene polymer (A1), which is a 4-methyl-1-pentene polymer (A) that has not been graft-modified; The laminate according to any one of [1] to [8], having the following in this order:

[0016]

[10] An article comprising the laminate according to any one of [1] to [9]. Effect of the Invention

[0017] According to the present invention, there is provided a laminate in which a layer which maintains the transparency of glass, is excellent in water repellency and heat resistance, and has excellent residual properties, is laminated on the surface of glass. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] <Laminate> The laminate of the present invention comprises a substrate layer (I) having a surface containing glass; a resin layer (II) having a thickness of 10 μm or less, which is formed from a composition (X) containing a 4-methyl-1-pentene polymer (A) satisfying the following requirement (a), and which is in contact with the surface; has.

[0019] <Resin layer (II)> [4-Methyl-1-pentene polymer (A)] The resin layer (II) contains a 4-methyl-1-pentene polymer (A). The 4-methyl-1-pentene polymer (A) has excellent water repellency, and the 4-methyl-1-pentene polymer (A) hardly migrates to a counter material in contact with the layer containing the 4-methyl-1-pentene polymer (A), and does not cause contamination of the counter material (i.e., the 4-methyl-1-pentene polymer (A) has good residual properties on the substrate layer (I)). In the laminate of the present invention, the resin layer (II) has excellent water repellency and residual properties because the resin layer (II) obtains water repellency by the 4-methyl-1-pentene polymer (A).

[0020] In this specification, the 4-methyl-1-pentene polymer (A) includes both an unmodified 4-methyl-1-pentene polymer (A1) that is not modified by a functional group and a modified 4-methyl-1-pentene polymer (A2) that is modified by a functional group. When the 4-methyl-1-pentene polymer (A) is described without specifying whether it is the unmodified 4-methyl-1-pentene polymer (A1) or the modified 4-methyl-1-pentene polymer (A2), the 4-methyl-1-pentene polymer (A) may be either the unmodified 4-methyl-1-pentene polymer (A1) or the modified 4-methyl-1-pentene polymer (A2). In the following description, the structural unit derived from 4-methyl-1-pentene in the 4-methyl-1-pentene polymer (A) may be referred to as "structural unit (i)". Similarly, the structural unit derived from ethylene or an α-olefin having 3 to 20 carbon atoms (excluding 4-methyl-1-pentene) in the 4-methyl-1-pentene polymer (A) may be referred to as "structural unit (ii)".

[0021] The 4-methyl-1-pentene polymer (A) contained in the resin layer (II) satisfies the following requirement (a).

[0022] [Requirement (a)] The melting point (Tm) measured with a differential scanning calorimeter (DSC) by the method described in the Examples below is greater than 180° C. and not greater than 220° C. The melting point (Tm) value (lower limit) can be, for example, 185° C. or more, 190° C. or more, 195° C. or more, 200° C. or more, 205° C. or more, or 210° C. or more. The melting point (Tm) value (upper limit) can be, for example, 215° C. or less, 210° C. or less, 205° C. or less, 200° C. or less, 195° C. or less, or 190° C. or less. The lower limit and the upper limit of the melting point (Tm) can be combined in any desired manner. That is, the melting point (Tm) can be, for example, 185 to 215°C, or 200 to 205°C.

[0023] When the melting point (Tm) measured by a differential scanning calorimeter (DSC) exceeds 180°C, the resin layer (II) formed from the composition (X) containing the 4-methyl-1-pentene polymer (A) has good heat resistance. Also, when the melting point (Tm) is 220°C or less, it is more easily dissolved in a solvent that can be used when preparing a coating agent than a 4-methyl-1-pentene polymer having a melting point (Tm) exceeding 220°C. Therefore, the properties of a coating agent prepared using a 4-methyl-1-pentene polymer (A) having a melting point (Tm) within the above range tend to be uniform, and the resin layer (II) tends to be easily formed using the coating agent. The melting point (Tm) value tends to depend on the stereoregularity of the 4-methyl-1-pentene polymer (A) and the type and content of the structural unit (ii) in the 4-methyl-1-pentene polymer (A). Therefore, the melting point (Tm) can be adjusted by using an olefin polymerization catalyst described later and further controlling the content and type of the structural unit (ii).

[0024] The 4-methyl-1-pentene polymer (A) preferably satisfies the following requirement (b). [Requirement (b)] The endothermic end temperature (TmE) in the melting (endothermic) curve measured by a differential scanning calorimeter (DSC) according to the method described in the Examples below is 230° C. or lower.

[0025] The endothermic end temperature (TmE) value (upper limit) can be, for example, 225° C. or lower, 220° C. or lower, 215° C. or lower, or 210° C. or lower. The endothermic end temperature (TmE) value (lower limit) can be, for example, 200° C. or higher, 205° C. or higher, 210° C. or higher, 215° C. or higher, 220° C. or higher, or 225° C. or higher. The lower limit and the upper limit of the endothermic temperature (TmE) can be combined arbitrarily. That is, the endothermic temperature (TmE) can be set to, for example, 200 to 230°C, or 210 to 215°C. Here, the endothermic temperature means the temperature at which melting is completed. The endothermic temperature and the heat generation start temperature described below are indicators different from the onset and offset, which are generally the intersection points between the baseline and the tangent to the steady line. The endothermic end temperature can be adjusted to a desired value, for example, by appropriately selecting an olefin polymerization catalyst for polymerizing the 4-methyl-1-pentene polymer (A) and by controlling the type and content of the structural unit (ii).

[0026] The 4-methyl-1-pentene polymer (A) having an endothermic end temperature in the above range has excellent heat resistance. Therefore, the resin layer (II) formed from the composition (X) containing the 4-methyl-1-pentene polymer (A) having an endothermic end temperature in the above range also tends to have excellent heat resistance. In addition, the 4-methyl-1-pentene polymer (A) having an endothermic end temperature in the above range is more easily dissolved in a solvent that can be used when preparing a coating agent than a 4-methyl-1-pentene polymer having an endothermic end temperature not in the above range. Therefore, the properties of the coating agent prepared using the 4-methyl-1-pentene polymer (A) having an endothermic end temperature in the above range tend to be uniform, and the resin layer (II) tends to be easily formed using the coating agent.

[0027] The 4-methyl-1-pentene polymer (A) preferably satisfies the following requirement (c).

[0028] [Requirement (c)] The exothermic onset temperature (TcS) in the crystallization (exothermic) curve measured with a differential scanning calorimeter (DSC) by the method described in the Examples below is 210° C. or lower. The value (upper limit) of the heat generation onset temperature (TcS) can be, for example, 205° C. or less, 200° C. or less, 195° C. or less, 190° C. or less, 185° C. or less, 180° C. or less, 175° C. or less, or 170° C. or less. The value (lower limit) of the heat generation onset temperature (TcS) can be, for example, 165° C. or more, 170° C. or more, 175° C. or more, 180° C. or more, 185° C. or more, 190° C. or more, or 195° C. or more. The lower limit and the upper limit of the heat generation onset temperature (TcS) can be combined in any desired manner. That is, the heat generation onset temperature (TcS) can be set to, for example, 165 to 200°C, or 165 to 185°C. The exotherm onset temperature (TcS) can be adjusted to a desired value, for example, by appropriately selecting an olefin polymerization catalyst for polymerizing the 4-methyl-1-pentene polymer (A) and by controlling the type and content of the structural unit (ii).

[0029] The 4-methyl-1-pentene polymer (A) having a heat generation onset temperature (TcS) in the above range is excellent in heat resistance. Therefore, the resin layer (II) formed from the composition (X) containing the 4-methyl-1-pentene polymer (A) having a heat generation onset temperature in the above range also tends to be excellent in heat resistance. In addition, the 4-methyl-1-pentene polymer (A) having a heat generation onset temperature in the above range is more easily dissolved in a solvent that can be used when preparing a coating agent than a 4-methyl-1-pentene polymer having a heat generation onset temperature not in the above range. Therefore, the properties of the coating agent prepared using the 4-methyl-1-pentene polymer (A) having a heat generation onset temperature in the above range tend to be uniform, and the resin layer (II) tends to be easily formed using the coating agent.

[0030] The 4-methyl-1-pentene polymer (A) used in the laminate of the present invention more preferably satisfies the requirements (a), (b) and (c). The 4-methyl-1-pentene polymer (A) satisfying the requirements (a) to (c) has good heat resistance and excellent solubility in a solvent, and is therefore likely to remain dissolved in the solvent. Therefore, the 4-methyl-1-pentene polymer (A) satisfying the requirements (a) to (c) has better storage stability when dissolved in a solvent than a 4-methyl-1-pentene polymer that does not satisfy any one or more of the requirements (a) to (c). That is, by dissolving the composition (X) containing the 4-methyl-1-pentene polymer (A) satisfying the requirements (a) to (c), a coating agent having more uniform properties and better storage stability can be produced. As a result, the resin layer (II) formed on the surface of the substrate layer (I) using the coating agent has more uniform properties. Moreover, a coating agent in which the composition (X) containing the 4-methyl-1-pentene polymer (A) is dissolved can be easily laminated on the substrate layer (I). Furthermore, in the laminate of the present invention, the resin layer (II) formed from the coating agent having the composition (X) dissolved therein is laminated on the substrate layer (I), and thus the water repellency of the glass surface of the substrate layer (I) is improved compared to a laminate in which the substrate layer (I) is exposed on the surface.

[0031] The 4-methyl-1-pentene polymer (A) may further satisfy one or more of the following requirements (d) to (g), and more preferably satisfies two or more of the following requirements (d) to (g).

[0032] [Requirement (d)] The 4-methyl-1-pentene polymer (A) has an intrinsic viscosity [η] of 0.5 to 6.0 dl / g, measured in decalin at 135° C. by the method described in the Examples below. The value (lower limit) of the intrinsic viscosity [η] is, for example, 0.6 dl / g or more, 0.7 dl / g or more, 0.8 dl / g or more, 0.9 dl / g or more, 1.0 dl / g or more, 1.1 dl / g or more, 1.2 dl / g or more, 1.3 dl / g or more, 1.4 dl / g or more, 1.5 dl / g or more, 1.6 dl / g or more, 1.7 dl / g or more, 1.8 dl / g or more, 1.9 dl / g or more, or 2.0 dl / g or more. The value (upper limit) of the intrinsic viscosity [η] is, for example, 5.5 dl / g or less, 5.0 dl / g or less, 4.5 dl / g or less, 4.0 dl / g or less, 3.5 dl / g or less, 3.0 dl / g or less, 2.5 dl / g or less, 2.4 dl / g or less, 2.2 dl / g or less, 2.0 dl / g or less, 1.8 dl / g or less, 1.6 dl / g or less, 1.4 dl / g or less, 1.2 dl / g or less, or 1.0 dl / g or less. The lower limit and the upper limit of the intrinsic viscosity [η] can be arbitrarily combined. That is, the intrinsic viscosity [η] can be, for example, 0.5 to 6.0 dl / g, or 0.8 to 1.2 dl / g. The 4-methyl-1-pentene polymer (A) having a limiting viscosity [η] within the above range has better heat resistance. Therefore, the resin layer (II) formed from the composition (X) containing the 4-methyl-1-pentene polymer (A) satisfying the requirement (d) tends to have good heat resistance. In addition, the coating agent obtained by dissolving the composition (X) containing the 4-methyl-1-pentene polymer (A) having a limiting viscosity [η] within the above range has better coatability and is suitable for forming the resin layer (II). The coating agent containing a polymer having a limiting viscosity [η] within the range of 0.5 to 6.0 dl / g may have better coatability, such as being less likely to form lumps when applied, being more likely to have a uniform coated surface, and being more likely to be applied smoothly over a wide area. The intrinsic viscosity [η] can be adjusted, for example, by the amount of hydrogen added in the polymerization step for producing the 4-methyl-1-pentene polymer (A).

[0033] [Requirement (e)] In the 4-methyl-1-pentene polymer (A), if a structural unit derived from 4-methyl-1-pentene is defined as a "structural unit (i)" and a structural unit derived from ethylene or an α-olefin having 3 to 20 carbon atoms (excluding 4-methyl-1-pentene) is defined as a "structural unit (ii)", the 4-methyl-1-pentene polymer (A) preferably satisfies the following (e1) and (e2). (e1) The amount (U1) of the structural unit (i) in the 4-methyl-1-pentene polymer (A) is preferably 84.0 to 100.0 mol % (wherein the total of the structural units (i) and (ii) is 100 mol %). (e2) The amount (U2) of the structural unit (ii) in the 4-methyl-1-pentene polymer (A) is preferably 0.0 to 16.0 mol % (where the total of the structural units (i) and (ii) is 100 mol %).

[0034] The amount (U1) of the structural unit (i) (lower limit) can be, for example, 88.0 mol% or more, 92.0 mol% or more, 94.0 mol% or more, 94.5 mol% or more, 95.0 mol% or more, 95.5 mol% or more, 96.0 mol% or more, 96.5 mol% or more, 97.0 mol% or more, or 97.5 mol% or more. The amount (U1) of the structural unit (i) (upper limit) can be, for example, 99.0 mol% or less, 98.5 mol% or less, 98.0 mol% or less, 97.5 mol% or less, 97.0 mol% or less, 96.5 mol% or less, 96.0 mol% or less, 95.5 mol% or less, 95.0 mol% or less, or 94.5 mol% or less. The lower limit and upper limit of the amount (U1) of the structural unit (i) can be combined in any desired manner. That is, the amount (U1) of the structural unit (i) can be, for example, 94.0 to 98.0 mol %, or 96.0 to 97.0 mol %.

[0035] The amount (U2) of the structural unit (ii) (lower limit) can be, for example, 1.0 mol% or more, 1.5 mol% or more, 2.0 mol% or more, 2.5 mol% or more, 3.0 mol% or more, 3.5 mol% or more, 4.0 mol% or more, 4.5 mol% or more, 5.0 mol% or more, or 5.5 mol% or more. The amount (U2) of the structural unit (ii) (upper limit) can be, for example, 12.0 mol% or less, 8.0 mol% or less, 6.0 mol% or less, 5.5 mol% or less, 5.0 mol% or less, 4.5 mol% or less, 4.0 mol% or less, 3.5 mol% or less, 3.0 mol% or less, or 2.5 mol% or less. The lower limit and upper limit of the amount (U2) of the structural unit (ii) can be arbitrarily combined. That is, the amount (U2) of the structural unit (ii) can be, for example, 2.0 to 6.0 mol%, or 3.0 to 4.0 mol%. (However, the total of the structural unit (i) and the structural unit (ii) is 100 mol%).

[0036] Incidentally, U1 and U2 are determined by the method described in the Examples. The 4-methyl-1-pentene polymer (A) having U1 and U2 in the above ranges is excellent in heat resistance and residual property. Therefore, the resin layer (II) formed from the composition (X) containing the 4-methyl-1-pentene polymer (A) having U1 and U2 in the above ranges also tends to be excellent in heat resistance and residual property.

[0037] The α-olefin from which the structural unit (ii) is derived may be a linear α-olefin. Examples of the α-olefin from which the structural unit (ii) is derived include ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-heptadecene, 1-octadecene, and 1-eicosene. Among these, from the viewpoint of heat resistance and residual property, linear α-olefins having 6 to 18 carbon atoms are preferred. Specifically, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-heptadecene, 1-octadecene, etc. are preferred, and among these, 1-decene, 1-hexadecene, and 1-octadecene are particularly preferred. The structural unit (ii) may be derived from only one selected from the group consisting of ethylene or α-olefins having 3 to 20 carbon atoms, or may be derived from two or more selected from the group consisting of ethylene or α-olefins having 3 to 20 carbon atoms.

[0038] Here, the 4-methyl-1-pentene polymer (A) may be a copolymer consisting of only the structural unit (i) and the structural unit (ii), in which case the total of the structural unit (i) and the structural unit (ii) is 100 mol %.

[0039] The 4-methyl-1-pentene polymer (A) may further contain, in addition to the structural units (i) and (ii), structural units derived from other polymerizable monomers other than 4-methyl-1-pentene, ethylene, and an α-olefin having 3 to 20 carbon atoms, as long as the amount is small enough not to impair the object of the present invention, specifically 10 mol % or less, preferably 5 mol % or less, and more preferably 3 mol % or less. The constituent units derived from other polymerizable monomers contained in the 4-methyl-1-pentene polymer (A) may be of one type or of two or more types. The 4-methyl-1-pentene, ethylene, and α-olefins having 3 to 20 carbon atoms, as well as other polymerizable monomers, may be derived from fossil raw materials, or may be derived from animal or plant raw materials.

[0040] Specific preferred examples of such other polymerizable monomers include vinyl compounds having a cyclic structure, such as styrene, vinylcyclopentane, vinylcyclohexane, and vinylnorbornane; vinyl esters, such as vinyl acetate; unsaturated organic acids or derivatives thereof, such as maleic anhydride; conjugated dienes, such as butadiene, isoprene, pentadiene, and 2,3-dimethylbutadiene; 1,4-hexadiene, 1,6-octadiene, 2-methyl-1,5-hexadiene, 6-methyl-1,5-heptadiene, 7-methyl-1,6-octadiene, and the like. Examples of non-conjugated polyenes include dienes, dicyclopentadiene, cyclohexadiene, dicyclooctadiene, methylenenorbornene, 5-vinyl-2-norbornene, 5-ethylidene-2-norbornene, 5-methylene-2-norbornene, 5-isopropylidene-2-norbornene, 6-chloromethyl-5-isopropenyl-2-norbornene, 2,3-diisopropylidene-5-norbornene, 2-ethylidene-3-isopropylidene-5-norbornene, and 2-propenyl-2,2-norbornadiene.

[0041] Here, when the 4-methyl-1-pentene polymer (A) contains a structural unit derived from another polymerizable monomer, it is preferable that the total content of the structural unit (ii) and the structural unit derived from the other polymerizable monomer is within the range of the content of the structural unit (ii).In this case, the total of the structural unit (i), the structural unit (ii), and the structural unit derived from the other polymerizable monomer is 100 mol%.

[0042] [Requirement (f)] The crystallization temperature (Tc) determined by a differential scanning calorimeter (DSC) according to the method described in the Examples below is 110 to 200°C.

[0043] The value (upper limit) of the crystallization temperature (Tc) can be, for example, 195° C. or less, 190° C. or less, 185° C. or less, 180° C. or less, 175° C. or less, 170° C. or less, 165° C. or less, 160° C. or less, or 155° C. or less. The value (lower limit) of the crystallization temperature (Tc) can be, for example, 120° C. or more, 130° C. or more, 140° C. or more, 150° C. or more, 155° C. or more, 160° C. or more, 165° C. or more, 170° C. or more, 175° C. or more, or 180° C. or more. The lower limit and the upper limit of the crystallization temperature (Tc) can be combined in any desired manner. That is, the crystallization temperature (Tc) can be set, for example, from 150 to 185°C, or from 150 to 175°C.

[0044] The crystallization temperature can be adjusted to a desired value, for example, by appropriately selecting an olefin polymerization catalyst for polymerizing the 4-methyl-1-pentene polymer (A) and by controlling the content of the structural unit (ii). A 4-methyl-1-pentene polymer (A) having a crystallization temperature in the above range is preferred from the viewpoint of heat resistance. Therefore, the resin layer (II) formed from the composition (X) containing the 4-methyl-1-pentene polymer (A) satisfying the requirement (f) tends to have good heat resistance. In addition, the coating agent obtained from the composition (X) containing the 4-methyl-1-pentene polymer (A) having a crystallization temperature in the above range tends to have better properties and storage stability. As a result, the resin layer (II) formed on the surface of the substrate layer (I) using the coating agent has uniform properties.

[0045] [Requirement (g)] The 4-methyl-1-pentene polymer (A) is preferably a modified 4-methyl-1-pentene polymer (A2) modified with a functional group. The modified 4-methyl-1-pentene polymer (A2) is preferably a graft modified product.

[0046] When the unmodified 4-methyl-1-pentene polymer, which is the raw material for the modified 4-methyl-1-pentene polymer (A2), is modified, an ethylenically unsaturated monomer having a functional group is used. The ethylenically unsaturated monomer used for modification is preferably an unsaturated carboxylic acid and / or a derivative thereof. Examples of the unsaturated carboxylic acid and / or a derivative thereof include an unsaturated compound having one or more carboxylic acid groups, an ester of a compound having a carboxylic acid group and an alkyl alcohol, and an unsaturated compound having one or more carboxylic acid anhydride groups.

[0047] Examples of the unsaturated group of the unsaturated compound include a vinyl group, a vinylene group, and an unsaturated cyclic hydrocarbon group. The unsaturated carboxylic acid and / or its derivative can be used alone or in combination of two or more. Among these ethylenically unsaturated monomers, unsaturated dicarboxylic acids or their acid anhydrides are preferred, and maleic acid, nadic acid, or their acid anhydrides are particularly preferred.

[0048] The method of graft-modifying the unmodified 4-methyl-1-pentene polymer, which is the raw material of the modified 4-methyl-1-pentene polymer (A2), with an ethylenically unsaturated monomer is not particularly limited, and a conventionally known graft polymerization method such as a solution method, a melt kneading method, etc. can be adopted. For example, there is a method of melting the unmodified 4-methyl-1-pentene polymer (A1) and adding an ethylenically unsaturated monomer to perform graft modification, or a method of dissolving the unmodified 4-methyl-1-pentene polymer (A1) in a solvent to prepare a solution, and adding an ethylenically unsaturated monomer thereto to perform graft modification.

[0049] The graft modification amount of the modified 4-methyl-1-pentene polymer (A2) is preferably 0.1 to 5.0 mass%, more preferably 0.4 to 3.0 mass%, further preferably 0.8 to 2.0 mass%, and further preferably 1.2 to 1.8 mass%, based on 100 mass% of the mass of the modified 4-methyl-1-pentene polymer (A2). When the graft modification amount of the modified 4-methyl-1-pentene polymer (A2) is within the above range, the adhesion between the resin layer (II) obtained from the composition (X) containing the modified 4-methyl-1-pentene polymer (A2) and the substrate layer (I) tends to be excellent.

[0050] [Method for producing 4-methyl-1-pentene polymer (A)] When the 4-methyl-1-pentene polymer (A) is an unmodified 4-methyl-1-pentene polymer (A1), the unmodified 4-methyl-1-pentene polymer (A1) can be obtained by polymerizing 4-methyl-1-pentene, a specific olefin from which the above-mentioned structural unit (ii) is derived, and further, if necessary, the other polymerizable monomer, in the presence of an olefin polymerization catalyst, by a known method.

[0051] Examples of the olefin polymerization catalyst that can be used in the production of the unmodified 4-methyl-1-pentene polymer (A1) include metallocene catalysts.Preferred metallocene catalysts include those described in WO 01 / 53369, WO 01 / 27124, JP-A-3-193796, JP-A-02-41303, WO 06 / 025540, or WO 2014 / 123212.

[0052] The unmodified 4-methyl-1-pentene polymer (A1) may be an unmodified 4-methyl-1-pentene polymer (A1) prepared so as to satisfy the requirement (a) by heat-treating a 4-methyl-1-pentene polymer once produced using the catalyst or the like in an extruder, mixer, etc. Alternatively, the unmodified 4-methyl-1-pentene polymer (A1) may be an unmodified 4-methyl-1-pentene polymer (A1) prepared so as to satisfy the requirement (a) by heat-treating a commercially available 4-methyl-1-pentene polymer (e.g., TPX manufactured by Mitsui Chemicals, Inc.) in an extruder, mixer, etc.

[0053] When the 4-methyl-1-pentene polymer (A) is a modified 4-methyl-1-pentene polymer (A2), the modified 4-methyl-1-pentene polymer (A2) is produced by modifying the unmodified 4-methyl-1-pentene polymer as a raw material by the above-mentioned modification method. The unmodified 4-methyl-1-pentene polymer as a raw material for the modified 4-methyl-1-pentene polymer (A2) may be the unmodified 4-methyl-1-pentene polymer (A1) or an unmodified 4-methyl-1-pentene polymer that does not fall under the unmodified 4-methyl-1-pentene polymer (A1).

[0054] [Composition (X)] In this specification, the composition (X) in which the 4-methyl-1-pentene polymer (A) contained in the composition (X) is an unmodified 4-methyl-1-pentene polymer (A1) may be referred to as the composition (X1). In addition, the composition (X) in which the 4-methyl-1-pentene polymer (A) contained in the composition (X) contains a modified 4-methyl-1-pentene polymer (A2) may be referred to as the composition (X2). For example, the composition (X) containing both the unmodified 4-methyl-1-pentene polymer (A1) and the modified 4-methyl-1-pentene polymer (A2) is the composition (X2). Note that, when either the composition (X1) or the composition (X2) is not specified, the composition (X) may be either the composition (X1) or the composition (X2). The 4-methyl-1-pentene polymer (A) may be contained in the composition (X) in one kind alone or in two or more kinds. Here, the composition (X) may contain one or more unmodified 4-methyl-1-pentene polymers (A1), may contain one or more modified 4-methyl-1-pentene polymers (A2), or may contain one or more unmodified 4-methyl-1-pentene polymers (A1) and one or more modified 4-methyl-1-pentene polymers (A2).

[0055] The composition (X) contains a 4-methyl-1-pentene polymer (A) and optionally contains other components such as an isocyanate compound (B). More preferably, the composition (X) contains a modified 4-methyl-1-pentene polymer (A2) that is a graft modified product, and further contains an isocyanate compound (B).

[0056] The content of the 4-methyl-1-pentene polymer (A) in the composition (X) is preferably 50 to 100% by mass, more preferably 60 to 100% by mass, and even more preferably 70 to 100% by mass. When the content of the 4-methyl-1-pentene polymer (A) in the composition (X) is within the above range, the water repellency and mechanical strength of the resulting laminate are excellent. In addition, the 4-methyl-1-pentene polymer (A) hardly migrates to the counter material in contact with the layer containing the 4-methyl-1-pentene polymer (A) (i.e., the residual property on the substrate layer (I) is good), so that the residual property of the resin layer (II) obtained from the composition (X) having the content of the 4-methyl-1-pentene polymer (A) within the above range is also good.

[0057] [Isocyanate compound (B)] The composition (X) may contain an isocyanate compound (B). In particular, when the 4-methyl-1-pentene polymer (A) in the composition (X) is a modified 4-methyl-1-pentene polymer (A2), it is preferable that the composition (X) contains an isocyanate compound (B) from the viewpoint of adhesion between the resin layer (II) and the base layer (I). The isocyanate compound (B) is not particularly limited as long as it is a compound having an isocyanate group. From the viewpoint of improving the adhesion between the resin layer (II) and the base layer (I), it is preferable that the isocyanate compound (B) is a polyfunctional isocyanate compound having two or more isocyanate groups in one molecule.

[0058] Examples of bifunctional isocyanate compounds having two isocyanate groups in one molecule include aliphatic diisocyanates such as methylene diisocyanate, dimethylene diisocyanate, trimethylene diisocyanate, tetramethylene diisocyanate, pentamethylene diisocyanate, hexamethylene diisocyanate, dipropyl ether diisocyanate, 2,2-dimethylpentane diisocyanate, 3-methoxyhexane diisocyanate, octamethylene diisocyanate, 2,2,4-trimethylpentane diisocyanate, nonamethylene diisocyanate, decamethylene diisocyanate, 3-butoxyhexane diisocyanate, 1,4-butylene glycol dipropyl ether diisocyanate, and thiodihexyl diisocyanate; Aromatic diisocyanates such as m-phenylene diisocyanate, p-phenylene diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, dimethylbenzene diisocyanate, ethylbenzene diisocyanate, isopropylbenzene diisocyanate, tolidine diisocyanate, 1,4-naphthalene diisocyanate, 1,5-naphthalene diisocyanate, 2,6-naphthalene diisocyanate, 2,7-naphthalene diisocyanate, metaxylylene diisocyanate, paraxylylene diisocyanate, and tetramethylxylylene diisocyanate; and Examples of the diisocyanate include alicyclic diisocyanates such as hydrogenated xylylene diisocyanate, isophorone diisocyanate, and dicyclohexylmethane 4,4'-diisocyanate.

[0059] The isocyanate compound (B) may be a biuret or isocyanurate, which is a trimer of a difunctional isocyanate compound, an adduct between a polyol such as trimethylolpropane and a difunctional isocyanate compound (i.e., an adduct), or an adduct between an alcohol such as methanol and a difunctional isocyanate compound (i.e., an allophanate).

[0060] Among these, from the viewpoint of preventing discoloration of the laminate, the isocyanate compound (B) is preferably an aliphatic isocyanate compound, more preferably an aliphatic isocyanate compound having two or more isocyanate groups in one molecule, further preferably an aliphatic diisocyanate, an isocyanurate of an aliphatic diisocyanate, an allophanate of an aliphatic diisocyanate and an alcohol, or an adduct of an aliphatic diisocyanate and a polyol, and particularly preferably an aliphatic diisocyanate or an isocyanurate of an aliphatic diisocyanate.

[0061] The isocyanate compound (B) may be a commercially available product. Examples of commercially available products include the Takenate series, such as Takenate D103H, D204, D160N, D170N, D165N, D178NL, D110N, and D370N (manufactured by Mitsui Chemicals, Inc.), and Coronate HX, HXR, HXL, HXLV, HK, HK-T, HL, and 2096 (manufactured by Nippon Polyurethane Industry Co., Ltd.).

[0062] When the composition (X) contains an isocyanate compound (B), the content is usually 2.00 parts by mass or less, preferably 1.50 parts by mass or less, based on 100 parts by mass of the 4-methyl-1-pentene polymer (A). When the composition (X) contains an isocyanate compound (B), the lower limit of the content of the isocyanate compound (B) is not particularly limited, but is usually 0.001 parts by mass or more based on 100 parts by mass of the 4-methyl-1-pentene polymer (A). The isocyanate compound (B) may be contained in the composition (X) either alone or in combination of two or more.

[0063] [Other components contained in composition (X)] The composition (X) may further contain, as necessary, antioxidants, heat stabilizers, weather stabilizers, antistatic agents, slip agents, leveling agents, reinforcing agents, antiblocking agents, antifogging agents, lubricants, dyes, pigments, natural oils, synthetic oils, waxes, fillers, etc., within the scope of the present invention. The composition (X) may contain a silicone-based polymer within the scope of the present invention, but the composition (X) may not contain a silicone-based polymer, and preferably the composition (X) does not contain a silicone-based polymer. The resin layer (II) formed from the composition (X) may also contain other components contained in the composition (X). The amount of the other components may be any amount that does not impair the object of the present invention, but the total amount of the other components is usually 0.005 to 5 parts by mass, and preferably 0.01 to 3 parts by mass, per 100 parts by mass of the composition (X).

[0064] As the antioxidant, known antioxidants can be used, specifically, hindered phenol compounds, sulfur-based antioxidants, lactone-based antioxidants, organic phosphite compounds, organic phosphonite compounds, or combinations of several of these can be used.

[0065] Examples of lubricants include sodium, calcium, and magnesium salts of saturated or unsaturated fatty acids such as lauric acid, palmitic acid, oleic acid, and stearic acid, which can be used alone or in combination of two or more. The amount of such lubricants to be added is usually 0.01 to 3 parts by mass, and preferably about 0.1 to 2 parts by mass, per 100 parts by mass of the composition (X).

[0066] As the slip agent, it is preferable to use amides of saturated or unsaturated fatty acids such as lauric acid, palmitic acid, oleic acid, stearic acid, erucic acid, and hebenic acid, or bisamides of these saturated or unsaturated fatty acids. Among these, erucic acid amide and ethylene bisstearamide are particularly preferable. It is preferable to mix these fatty acid amides in the range of 0.01 to 5 parts by mass with respect to 100 parts by mass of the 4-methyl-1-pentene polymer (A).

[0067] Examples of antiblocking agents include finely divided silica, finely divided aluminum oxide, finely divided clay, tetrafluoroethylene resin, finely divided crosslinked resin, such as crosslinked acrylic or methacrylic resin powder, etc. Among these, finely divided silica and crosslinked acrylic or methacrylic resin powder are preferred.

[0068] In addition, when the resin layer (II) is formed using a coating agent in which the composition (X) is dissolved, as described below, it is also a preferred embodiment to add a leveling agent to the composition (X). As a leveling agent for reducing the surface roughness of the coating layer (II) formed using the coating agent, a fluorine-based nonionic surfactant, a special acrylic resin-based leveling agent, etc. can be used, and those having good compatibility with the solvent are preferred, and the amount added is in the range of 1 to 50,000 ppm relative to the 4-methyl-1-pentene polymer (A) in the composition (X).

[0069] Examples of the reinforcing agent include oxides of metals such as silicon, titanium, aluminum, and zirconium, clay minerals, polyfunctional alkoxy compounds, and oligomers thereof. When oxides of metals such as silicon, titanium, aluminum, and zirconium, clay minerals, and the like are used as reinforcing agents, the reinforcing agent can be blended in an amount of, for example, 5 to 10 parts by mass per 100 parts by mass of the 4-methyl-1-pentene polymer (A) in the composition (X). When polyfunctional alkoxy compounds or oligomers thereof are used as reinforcing agents, the reinforcing agent can be blended in an amount of, for example, 5 to 50 parts by mass per 100 parts by mass of the 4-methyl-1-pentene polymer (A) in the composition (X). This can increase the hardness and elastic modulus of the resin layer (II) formed from the composition (X). If the amount of the reinforcing agent added is less than 5 parts by mass, the effect is too low, and if it exceeds 10 parts by mass in the case of metal oxides or clay minerals, or 50 parts by mass in the case of polyfunctional alkoxy compounds or oligomers, the transparency or mechanical strength of the resin layer (II) may be impaired.

[0070] [Method for producing composition (X)] The composition (X) can be produced by mixing the 4-methyl-1-pentene polymer (A) with other components such as the isocyanate compound (B). Alternatively, instead of producing the composition (X) itself, a coating agent containing the composition (X) dissolved therein may be produced by dissolving all the components contained in the composition (X) in a solvent, and the coating agent may be dried to produce the composition (X).

[0071] [Thickness of resin layer (II)] The coating layer (II) included in the laminate of the present invention has a thickness of 10 μm or less, preferably 0.001 to 9.5 μm, more preferably 0.01 to 9.0 μm, even more preferably 0.01 μm or more and less than 4 μm, and particularly preferably 0.1 to 3 μm. When the thickness of the resin layer (II) is within the above range, the water repellency is excellent and the transparency of the glass surface included in the substrate layer (I) is not easily impaired. Even when the portion of the substrate layer (I) other than the glass is transparent, when the thickness of the resin layer (II) is within the above range, the transparency of the entire laminate is not easily impaired while the water repellency is excellent. The thickness of the resin layer (II) can be appropriately set depending on the application of the laminate and the method of forming the resin layer (II). For example, when the resin layer (II) is formed by applying a coating agent in which the composition (X) is dissolved to the substrate layer (I) with an applicator or the like, the thickness of the resin layer (II) can be adjusted by the concentration of the 4-methyl-1-pentene polymer (A) in the coating agent used. The lower the concentration of the 4-methyl-1-pentene polymer (A) contained in the coating agent, the thinner the thickness of the resulting coating layer (II) tends to be.

[0072] <Base material layer (I)> The substrate layer (I) contained in the laminate of the present invention contains glass, and glass is contained on the surface of the substrate layer (I). The material of the substrate layer (I) is not particularly limited as long as it has a surface containing glass. For example, the substrate layer (I) may be a layer made of only glass such as a plate glass, or may be a molded body obtained from a glass resin composite containing glass and a known resin, and at least a part of the surface of the molded body may contain a glass surface. The type of glass contained in the substrate layer (I) is not particularly limited, and examples thereof include soda-lime glass (soda glass), borate glass, aluminosilicate glass, lead glass, borosilicate glass, and quartz glass. In addition, the glass resin composite that can be used as the substrate layer (I) may be a glass resin composite containing a known resin and one or more selected from the group consisting of glass spheres, hollow glass beads, and glass fibers, and may include a surface made of glass. For example, such a glass resin composite may be a mixture of a resin and hollow glass beads in order to reduce the weight of the resin composite, or may be a mixture of a resin composite and glass fibers. Furthermore, a molded body obtained from a resin composition that may be a glass resin composite, in which glass is used on a part of the surface, may be used as the substrate layer (I). The thickness of the base layer (I) can be appropriately set depending on the application of the laminate. The thickness of the base layer (I) can be, for example, from 1 μm to 10 mm, and can be from 1 to 5 mm.

[0073] The method of forming the substrate layer (I) is not particularly limited. For example, when the substrate layer (I) is a plate glass, a mixture containing a main raw material such as silica or alumina, an antifoaming agent such as mirabilite or antimony oxide, and a reducing agent such as carbon is melted at 1400 to 1600 ° C., formed into a plate shape, and then cooled to produce the substrate layer (I). The produced substrate layer (I) may be chemically polished with a solvent such as hydrofluoric acid as necessary to make it thinner or to improve its smoothness. The substrate layer (I) may be a commercially available plate glass or a glass resin composite as it is, or may be a commercially available thin glass plate polished to a desired thickness. In addition, when the substrate layer (I) is a substrate layer in which glass is used on a part of the surface of a molded body obtained from a resin composition, for example, a glass plate, glass spheres, hollow glass beads, glass fibers, etc. may be bonded to the molded body of the resin composition with a known adhesive or the like to form the substrate layer (I).

[0074] <Laminate> The laminate of the present invention includes the above-mentioned substrate layer (I) and resin layer (II). The resin layer (II) may be a layer formed from a composition (X1) containing an unmodified 4-methyl-1-pentene polymer (A1), or may be formed from a composition (X2) containing a modified 4-methyl-1-pentene polymer (A2).

[0075] The laminate of the present invention may include the above-mentioned substrate layer (I) and resin layer (II). For example, the laminate may have the substrate layer (I), the resin layer (II), and the resin layer (III) formed from the composition (X) containing the 4-methyl-1-pentene polymer (A) and having a thickness of 10 μm or less, in this order. Here, the resin layer (III) may be a layer formed from the composition (X1) containing the unmodified 4-methyl-1-pentene polymer (A1), or may be formed from the composition (X2) containing the modified 4-methyl-1-pentene polymer (A2). Since the resin layer (III) is formed from the composition (X) containing the 4-methyl-1-pentene polymer (A), it has excellent water repellency and residual properties, similar to the resin layer (II). In addition, when the thickness of the resin layer (III) is 10 μm or less, the transparency of the glass surface of the laminate is not easily impaired by the resin layer (III). Furthermore, the laminate of the present invention may have two or more resin layers (III). When the laminate of the present invention includes a plurality of resin layers (III), these resin layers (III) may be the same or different. In addition, some of the resin layers (III) may be layers formed from a composition (X1) containing an unmodified 4-methyl-1-pentene polymer (A1), and the other layers may be layers formed from a composition (X2) containing a modified 4-methyl-1-pentene polymer (A2).

[0076] In one preferred embodiment of the laminate of the present invention, the resin layer (II) is a layer containing a modified 4-methyl-1-pentene polymer (A2) which is a graft modified product.

[0077] When the substrate layer (I) has a surface such as a glass plate, the laminate may have the resin layer (II) on only one surface of the substrate layer (I), or may have the resin layer (II) on both surfaces of the substrate layer (I). When the resin layer (II) is formed on only one surface of the substrate layer (I), if the thickness of the resin layer (II) is 10 μm or less, the transparency of the glass surface portion of the laminate is unlikely to be impaired. When the resin layer (II) is formed on both sides of the base layer (I), if the thickness of the resin layer (II) formed on each side is 10 μm or less (i.e., the total thickness of the resin layer (II) on both sides is 20 μm or less), the transparency of the glass part of the laminate is good on either side having the resin layer (II). Note that when the resin layer (II) is formed on both sides of the base layer (I), if the total thickness of the resin layer (II) on both sides is 10 μm or less, the transparency of the glass surface part of the laminate is less likely to be impaired. In addition, when the base layer (I) is a glass plate, and when a highly transparent material is used in parts other than the glass surface of the base layer (I) so that the entire base layer (I) has excellent transparency, the transparency of the entire laminate is less likely to be impaired by adjusting the thickness of the resin layer (II) to within the above range.

[0078] When the resin layer (II) is formed on only one side of the substrate layer (I), the resin layer (III) is formed on the side on which the resin layer (II) is formed. When the total thickness of the resin layer (III) and the resin layer (II) is 20 μm or less, the transparency of the glass surface portion of the laminate is not easily impaired. When the resin layer (II) is formed on both sides of the substrate layer (I), the resin layer (III) may be formed on only one of the sides on which the resin layer (II) is formed, or may be formed on both of the resin layers (II). When the total thickness of the resin layer (III) and the resin layer (II) formed on each side is 20 μm or less, the transparency of the glass portion is unlikely to be impaired on either side of the laminate. In addition, when the base layer (I) is a glass plate, and when a highly transparent material is used in parts other than the glass surface of the base layer (I) so that the entire base layer (I) has excellent transparency, the transparency of the entire laminate is less likely to be impaired by adjusting the thicknesses of the resin layer (II) and the resin layer (III) to within the above-mentioned ranges.

[0079] <<Method for manufacturing laminate>> The laminate of the present invention can be suitably produced, for example, by the following production method: That is, the laminate of the present invention can be produced by a method including a step (1) of preparing a coating agent in which the composition (X) is dissolved by mixing the 4-methyl-1-pentene polymer (A), a solvent (D), and optionally the isocyanate compound (B) and other components contained in the composition (X), and a step (2) of attaching the coating agent to a part or the entire surface of the base layer (I) using an applicator or the like, and removing the solvent (D) to form a resin layer (II). The laminate of the present invention can also be produced by a method including, after step (2), step (3) of preparing a coating agent in which a composition (X) containing a 4-methyl-1-pentene polymer (A) to be contained in the resin layer (III) is dissolved, and step (4) of forming a resin layer (III) by applying the coating agent containing the 4-methyl-1-pentene polymer (A) to be contained in the resin layer (III) to a part or the whole of the surface of the resin layer (II) using an applicator or the like and removing the solvent (D). Here, when the 4-methyl-1-pentene polymer (A) contained in the resin layer (II) and the 4-methyl-1-pentene polymer (A) contained in the resin layer (III) are the same polymer, step (3) may be a step of preparing the coating agent obtained in step (1).

[0080] [Coating agent containing composition (X) dissolved therein] The coating agent in which the composition (X) is dissolved is obtained by dissolving the composition (X) in a solvent (D). Therefore, the coating agent contains the components contained in the composition (X) used for preparing the coating agent and the solvent (D). For example, when the composition (X) contains 100% by mass of the 4-methyl-1-pentene polymer (A), the coating agent is obtained by dissolving the 4-methyl-1-pentene polymer (A) in the solvent (D). In addition, when the composition (X) used for preparing the coating agent contains an isocyanate compound (B) and other components in addition to the 4-methyl-1-pentene polymer (A), the resulting coating agent contains these substances.

[0081] The content of the 4-methyl-1-pentene polymer (A) in the coating agent in which the composition (X) is dissolved is usually 0.01 to 50 mass%, preferably 0.05 to 30 mass%, more preferably 0.07 to 25 mass%, further preferably 0.1 to 20 mass%, particularly preferably 0.2 to 20 mass%, and especially preferably 0.3 to 20 mass%. The content of the solvent (D) in the coating agent is usually 50 to 99.99 mass%, preferably 70 to 99.95 mass%, more preferably 75 to 99.93 mass%, further preferably 80 to 99.9 mass%, particularly preferably 80 to 99.8 mass%, and especially preferably 80 to 99.7 mass%.

[0082] When the contents of the 4-methyl-1-pentene polymer (A) and the solvent (D) in the coating agent are within the above ranges, a good balance is achieved between the handleability and the ease of removing the solvent (D) when forming the resin layer (II) from the coating agent.

[0083] [Solvent (D)] The solvent (D) is not particularly limited as long as it can dissolve the 4-methyl-1-pentene polymer (A) and the isocyanate compound (B), but an organic solvent can be preferably used. Here, the 4-methyl-1-pentene polymer (A) can be an unmodified 4-methyl-1-pentene polymer (A1) or a modified 4-methyl-1-pentene polymer (A2). Examples of the solvent (D) include aliphatic hydrocarbons such as n-hexane, n-heptane, n-octane, cyclohexane, methylcyclohexane, and ethylcyclohexane; and aromatic hydrocarbons such as toluene and xylene. Among these, toluene, cyclohexane, and methylcyclohexane can be preferably used.

[0084] [Method for producing a coating agent containing dissolved composition (X)] The method for producing the coating agent in which the composition (X) is dissolved is not particularly limited, and it can be produced by a commonly used method. For example, it can be produced by adding the 4-methyl-1-pentene polymer (A) to the solvent (D) and stirring for a predetermined time at a temperature below the boiling point of the solvent (D). In addition, the composition (X) can also be produced by heat-treating a separately prepared 4-methyl-1-pentene polymer to prepare the 4-methyl-1-pentene polymer (A), adding the obtained 4-methyl-1-pentene polymer (A) to the solvent (D), and stirring for a predetermined time at a temperature below the boiling point of the solvent (D). When the coating agent contains an isocyanate compound (B), the isocyanate compound (B) may be added to the solvent (D) in which the 4-methyl-1-pentene polymer (A) is dissolved. Also, the isocyanate compound (B) may be added to the solvent (D) before dissolving the 4-methyl-1-pentene polymer (A). In this case, the 4-methyl-1-pentene polymer (A) may be added to the solvent (D) in which the isocyanate compound (B) is dissolved. Furthermore, the 4-methyl-1-pentene polymer (A) and the isocyanate compound (B) may be added to the solvent (D) at the same time. Also, when the coating agent contains the other components other than the 4-methyl-1-pentene polymer (A) and the isocyanate compound (B), the timing at which the other components are added is also arbitrary.

[0085] [Step of forming resin layer (II)] An example of the treatment carried out in the step (step (2)) of forming the resin layer (II) will be described below. Specifically, in step (2), a coating agent in which the composition (X) is dissolved is attached to the surface of the substrate layer (I), and the coating agent is heated to a temperature close to the boiling point of the solvent (D) in the coating agent, thereby removing the solvent (D) in the composition (X) to a certain extent. The method for attaching the coating agent to the surface of the base layer (I) is not particularly limited, and examples thereof include application using a brush or paintbrush, spraying, screen printing, flow coating, spin coating, dipping, and application to a roll or flat plate using a bar coater, a T-die, a T-die with a bar, a doctor knife, a roll coater, a die coater, etc. Dipping includes a method of immersing one side of the base layer (I) in the coating agent, a method of immersing both sides of the base layer (I) in the coating agent, etc. In addition to the above, the 4-methyl-1-pentene polymer (A) can be molded into a film using a T-die cast film molding machine or the like to obtain a cast film, and the cast film and the base layer can be melt-bonded to form a resin layer (II) on the base layer (I).

[0086] In the present application, the removal of the solvent does not only mean the complete removal of the solvent (D) from the coating agent, but also includes the removal of the solvent (D) to such an extent that the 4-methyl-1-pentene polymer (A) contained in the coating agent can be formed as the resin layer (II). Specifically, the removal of the solvent includes the removal of the solvent until the solvent is about 0.001 to 0.5% by mass relative to 100% by mass of the resin layer (II) produced using the composition (X). The method for removing the solvent is not particularly limited, and the solvent may be dried by leaving it alone, but is generally removed by heating and drying at 30 to 220°C. In addition, in order to prevent thermal deterioration or thermal decomposition of the 4-methyl-1-pentene polymer (A), it is preferable to remove the solvent (D) at a temperature equal to or lower than the melting point (Tm) of the 4-methyl-1-pentene polymer (A). On the other hand, if the drying temperature is too low, the drying time will be long, which will deteriorate productivity, and if the drying temperature is too high, problems such as foaming and deterioration will occur. In order to dry in a short time while preventing foaming, the temperature may be increased in two or more stages or continuously while drying. In addition, the amount of solvent remaining in the resin layer (II) can be reduced by immersing the resin layer (II) in a solvent in which the 4-methyl-1-pentene polymer (A) is poorly soluble, such as water, methanol, ethanol, acetone, or methylene chloride, or by exposing the resin layer (II) to a vapor atmosphere of the solvent after the drying step. The amount of solvent remaining in the resin layer (II) after drying is 0.5% by mass or less, preferably 0.05% by mass or less, and more preferably 0.01% by mass or less.

[0087] [Step of forming resin layer (III) (step (4))] The resin layer (III) can be formed in the same manner as in the step of forming the resin layer (II), except that a coating agent in which the composition (X) prepared in the above step (3) is dissolved is used.

[0088] <Applications of laminate> The laminate of the present invention can be used in any known article without any particular limitation.

[0089] ≪Goods≫ The article of the present invention is not particularly limited as long as it includes the laminate of the present invention, and can be, for example, window materials for general buildings, high-rise buildings, etc.; platform doors; light collection from roofs; lighting covers; covers and substrates for solar cells; covering materials for agricultural greenhouses; window materials for vehicles such as automobiles and trains (particularly windshields in the case of automobile windows); window materials for machine tools and the like; substrates and cover glass for electronic devices; touch panels; advertising boards and guide boards that emit light in a planar manner; partitions; flexible laminates; glass lenses that can be used in optical instruments, etc.; glass antennas; analytical cells that can be used in analytical equipment, etc. EXAMPLES

[0090] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to these examples.

[0091] <Method of measuring physical properties of polymer> [composition] The amount of structural units (i) (the amount of structural units derived from 4-methyl-1-pentene, U1) and the amount of structural units (ii) (the amount of structural units derived from α-olefin, U2) in the 4-methyl-1-pentene polymer (A) were determined by the following apparatus and under the following conditions: 13 Calculated from C-NMR spectrum. The U1 and U2 in the modified 4-methyl-1-pentene polymer (A2) are almost the same as the amount of the structural unit (i) and the total amount of the structural unit (ii) contained in the unmodified 4-methyl-1-pentene polymer used as the raw material for the modified 4-methyl-1-pentene polymer (A2). Therefore, for the modified 4-methyl-1-pentene polymer (A2), the amount of the structural unit (i) and the total amount of the structural unit (ii) were determined appropriately using the unmodified 4-methyl-1-pentene polymer used as the raw material for the modified 4-methyl-1-pentene polymer (A2).

[0092] The nuclear magnetic resonance spectrometer used was a JEOL ECP500 type. The solvent was a mixture of o-dichlorobenzene / heavy benzene (80 / 20% by volume), the sample concentration was 55 mg / 0.6 mL, the measurement temperature was 120°C, and the observed nuclei were13 The measurements were performed using C (125 MHz), a sequence of single pulse proton decoupling, a pulse width of 4.7 μs (45° pulse), a repetition time of 5.5 s, and an accumulation count of 10,000 or more, with 27.50 ppm as the reference value for the chemical shift. 13 The composition of 4-methyl-1-pentene and α-olefins was quantified by C-NMR spectroscopy. The amounts of the structural units (i) and (ii) were determined in the same manner for the 4-methyl-1-pentene polymer used in the comparative examples described below.

[0093] [Intrinsic viscosity [η]] The intrinsic viscosity [η] was measured at 135° C. using decalin as a solvent. That is, about 20 mg of the 4-methyl-1-pentene polymer (A) as a sample was weighed out, dissolved in 15 mL of decalin, and the specific viscosity η sp The decalin solution was diluted with 5 mL of decalin solvent, and the specific viscosity η was measured in the same manner. sp This dilution procedure was repeated two more times, and the η sp The value of / C was calculated as the intrinsic viscosity (see the formula below). [η]=lim(η sp / C) (C→0) The intrinsic viscosity [η] of the 4-methyl-1-pentene polymer used in the comparative example described later was also determined in the same manner.

[0094] [Graft modification amount] The amount of graft modification of the modified 4-methyl-1-pentene polymer (A2) (i.e., the content of the structural units derived from the ethylenically unsaturated monomer used for modification when the mass of the modified 4-methyl-1-pentene polymer (A2) is taken as 100% by mass) was determined by the following method. First, the modified 4-methyl-1-pentene polymer (A2) as a sample was treated at 250°C with 5 minutes of preheating and 3 minutes of pressing to prepare a pressed film, and the pressed film was subjected to IR measurement by a transmission method using a Fourier transform infrared spectrophotometer (FT-IR410, manufactured by JASCO Corporation). In the following examples, maleic anhydride was used for graft modification, so that the peak at 1860 cm -1 and 4321 cm -1 The amount of graft modification was calculated from the peak intensity.

[0095] [Melting point (Tm), endothermic end temperature (TmE), exothermic start temperature (TcS), crystallization temperature (Tc)] Using a DSC measuring device (DSC220C) manufactured by Seiko Instruments Inc., an exothermic-endothermic curve was obtained in accordance with ASTM D3418, and the melting point (Tm) and crystallization temperature (Tc) were calculated as follows.

[0096] Approximately 5 mg of the sample was placed in a measurement aluminum pan, heated from 20°C to 280°C at a heating rate of 10°C / min, held at 280°C for 5 minutes, cooled to 20°C at a cooling rate of 10°C / min, held at 20°C for 5 minutes, and then heated again from 20°C to 280°C at a heating rate of 10°C / min. The crystallization peak that appeared during the first cooling was taken as the crystallization temperature (Tc). When multiple crystallization peaks were detected, the one with the highest temperature was taken as the crystallization temperature (Tc). The melting peak that appeared during the second heating was taken as the melting point (Tm). When multiple melting peaks were detected, the one with the highest temperature was taken as the melting point (Tm).

[0097] The temperature at which the endotherm of the melting (endotherm) curve ended was taken as the endotherm end temperature (TmE), and the temperature at which the heat generation of the crystallization (exotherm) curve started was taken as the exotherm start temperature (TcS).

[0098] The start and end points are the points at which it can be confirmed that the curve deviates from the baseline where the amount of heat becomes constant at the start or end of endothermic or exothermic reaction, and a difference in the amount of heat begins to appear.

[0099] <Preparation Example 1: Preparation of (8-octamethylfluoren-12'-yl-(2-(adamantan-1-yl)-8-methyl-3,3b,4,5,6,7,7a,8-octahydrocyclopenta[a]indene))zirconium dichloride> Using the method described in Preliminary Experiment 5 (paragraphs 0346 to 0348) of WO 2014 / 123212, (8-octamethylfluoren-12'-yl-(2-(adamantan-1-yl)-8-methyl-3,3b,4,5,6,7,7a,8-octahydrocyclopenta[a]indene))zirconium dichloride was synthesized.

[0100] <Production Example 1: Production of Polymer 1> 500 mL of 4-methyl-1-pentene and 220 mL of heptane were charged at 23°C into a 1.5 L stainless steel autoclave equipped with an agitator, which had been thoroughly purged with nitrogen. 30 mL of 1-decene and 0.3 mL of a 1.0 mmol / mL toluene solution of triisobutylaluminum (TIBAL) were then charged into the autoclave, and stirring was started. Next, 140 mL of hydrogen was charged into the autoclave, and the autoclave was heated to an internal temperature of 60°C. Thereafter, 2 mL of a toluene solution containing 0.039 mmol of liquid methylaluminoxane in terms of aluminum atom and 0.00013 mmol of the (8-octamethylfluoren-12'-yl-(2-(adamantan-1-yl)-8-methyl-3,3b,4,5,6,7,7a,8-octahydrocyclopenta[a]indene))zirconium dichloride obtained in Preparation Example 1 was injected into the autoclave under pressure with nitrogen to initiate polymerization. During the polymerization reaction, the temperature inside the autoclave was adjusted to 60°C. 10 minutes after the start of polymerization, 5 mL of methanol was injected into the autoclave with nitrogen to terminate the polymerization, and the autoclave was depressurized to atmospheric pressure. The reaction solution was poured into acetone with stirring to precipitate polymer 1. The obtained polymer 1 was dried at 130°C under reduced pressure for 10 hours. The content of structural units in polymer 1 was found to be 94.1 mol% of structural units derived from 4-methyl-1-pentene, and 5.9 mol% of structural units derived from α-olefin. The melting point (Tm) of polymer 1 was 190°C, and the intrinsic viscosity [η] (in decalin at 135°C) was 2.3 dl / g. Other physical properties of polymer 1 are shown in Table 1-1. In the following description, Table 1-1 and Table 1-2 are collectively referred to as Table 1.

[0101] <Production Example 2: Production of Polymer 2> 500 mL of 4-methyl-1-pentene and 230 mL of heptane were charged at 23°C into a 1.5 L stainless steel autoclave equipped with an agitator, which had been thoroughly purged with nitrogen. 20 mL of Linearene 168 (Idemitsu Kosan, a mixture of 1-hexadecene and 1-octadecene) and 0.3 mL of a 1.0 mmol / mL toluene solution of triisobutylaluminum (TIBAL) were then charged into the autoclave, and stirring was started. Next, 140 mL of hydrogen was charged, and the autoclave was heated to an internal temperature of 60°C. Thereafter, 2 mL of a toluene solution containing liquid methylaluminoxane at 0.033 mmol in terms of aluminum atom and further containing 0.00011 mmol of (8-octamethylfluoren-12'-yl-(2-(adamantan-1-yl)-8-methyl-3,3b,4,5,6,7,7a,8-octahydrocyclopenta[a]indene))zirconium dichloride obtained in Preparation Example 1 was injected into the autoclave under pressure with nitrogen to initiate polymerization. During the polymerization reaction, the temperature inside the autoclave was adjusted to 60°C. 13 minutes after the start of polymerization, 5 mL of methanol was injected into the autoclave with nitrogen to terminate the polymerization, and the autoclave was depressurized to atmospheric pressure. The reaction solution was poured into acetone with stirring to precipitate polymer 2. The obtained polymer 2 was dried at 130°C under reduced pressure for 10 hours. The content of structural units in polymer 2 was found to be 97.6 mol% of structural units derived from 4-methyl-1-pentene, and 2.4 mol% of the total of structural units derived from α-olefins. The melting point (Tm) of polymer 2 was 207°C, and the intrinsic viscosity [η] (in decalin at 135°C) was 2.4 dl / g. Other physical properties of polymer 2 are shown in Table 1.

[0102] <Production Example 3: Production of Polymer 3> 500 mL of 4-methyl-1-pentene and 230 mL of heptane were charged into a 1.5 L stainless steel autoclave equipped with an agitator, which had been thoroughly purged with nitrogen, at 23°C. 15 mL of 1-decene and 0.3 mL of a 1.0 mmol / mL toluene solution of triisobutylaluminum (TIBAL) were then charged into the autoclave, and stirring was started. Next, 140 mL of hydrogen was charged, and the autoclave was heated to an internal temperature of 60°C. Thereafter, 2 mL of a toluene solution containing 0.06 mmol of previously prepared liquid methylaluminoxane in terms of aluminum atom and 0.0002 mmol of the (8-octamethylfluoren-12'-yl-(2-(adamantan-1-yl)-8-methyl-3,3b,4,5,6,7,7a,8-octahydrocyclopenta[a]indene))zirconium dichloride obtained in Preparation Example 1 was injected into the autoclave under pressure with nitrogen to initiate polymerization. During the polymerization reaction, the temperature inside the autoclave was adjusted to 60°C. 30 minutes after the start of polymerization, 5 mL of methanol was injected into the autoclave with nitrogen to terminate the polymerization, and the autoclave was depressurized to atmospheric pressure. The reaction solution was poured into acetone with stirring to precipitate polymer 3. The obtained polymer 3 was dried at 130°C under reduced pressure for 10 hours. The content of structural units in polymer 3 was found to be 96.7 mol% derived from 4-methyl-1-pentene and 3.3 mol% derived from α-olefin. The melting point (Tm) of polymer 3 was 212°C, and the intrinsic viscosity [η] (in decalin at 135°C) was 2.3 dl / g. Other physical properties of polymer 3 are shown in Table 1.

[0103] <Production Example 4: Production of Polymer 4> [Synthesis Example 4-1: Production of olefin polymerization catalyst] At 30°C, in a three-neck flask equipped with a 200mL stirrer that had been thoroughly substituted with nitrogen, 30mL of purified decane and 14.65mmol of particulate solid polymethylaluminoxane with a D50 of 28μm and an aluminum atom content of 43% by mass (synthesized using the method described in International Publication No. 2014 / 123212) were charged under nitrogen gas flow to form a suspension. 50.0mg (0.0586mmol) of (8-octamethylfluoren-12'-yl-(2-(adamantan-1-yl)-8-methyl-3,3b,4,5,6,7,7a,8-octahydrocyclopenta[a]indene))zirconium dichloride obtained in Preparation Example 1 was added to the suspension as a 4.58mmol / L toluene solution while stirring. After 1 hour, stirring was stopped, and the resulting mixture was washed with 100 mL of decane by decantation, and then decane was added to make 50 mL of a slurry liquid (zirconium atom carrying rate: 98%).

[0104] [Synthesis Example 4-2: Preparation of prepolymerization catalyst component] To the slurry liquid prepared in Synthesis Example 4-1, 1.0 mL of a decane solution of triisobutylaluminum (TIBAL) (0.5 mmol / mL in terms of aluminum atom) was charged under a nitrogen gas flow at 25°C. After cooling to 15°C, 10 mL of 4-methyl-1-pentene was charged into the reactor over 60 minutes. The start of the charging of 4-methyl-1-pentene was regarded as the start of prepolymerization. Stirring was stopped 2.0 hours after the start of prepolymerization, and the resulting mixture was washed three times with 100 mL of decane by decantation. The prepolymerization catalyst component was a decane slurry (9.5 g / L, 0.56 mmol / L in terms of zirconium atom).

[0105] [Preparation of Polymer 4a] At room temperature and under a nitrogen stream, 425 mL of purified decane was placed in a SUS polymerization vessel equipped with a stirrer having an internal volume of 1 L, and the temperature was raised to 40°C. After reaching 40°C, 0.8 mL (0.4 mmol in terms of aluminum atoms) of a decane solution of triisobutylaluminum (TIBAL) (0.5 mmol / mL in terms of aluminum atoms) was charged, and then 0.00175 mmol in terms of zirconium atoms of the decane slurry of the prepolymerization catalyst component of Synthesis Example 4-2 was charged. 23.75 NmL of hydrogen was charged, and then a mixture of 230 mL of 4-methyl-1-pentene and 22.4 mL of Linearene 168 (Idemitsu Kosan, a mixture of 1-hexadecene and 1-octadecene) was continuously charged into the polymerization vessel at a constant rate over 2 hours. The start of the charging of the mixture was regarded as the start of polymerization, and the temperature was maintained at 45°C for 4.5 hours. 23.75 NmL of hydrogen was charged 1 hour and 2 hours after the start of polymerization. 4.5 hours after the start of polymerization, the temperature was lowered to room temperature, the pressure was released, and the polymerization liquid containing a white solid was immediately filtered to obtain a solid substance. This solid substance was dried under reduced pressure at 80°C for 8 hours to obtain polymer 4a. The yield was 142 g. The content of structural units in polymer 4a was 96.5 mol% derived from 4-methyl-1-pentene, and the total content of structural units derived from α-olefins was 3.5 mol%. Polymer 4a had a melting point (Tm) of 201°C and a limiting viscosity [η] (in decalin at 135°C) of 4.2 dl / g.

[0106] [Production of Polymer 4] Polymer 4a was mixed with 0.02 phr of the phenolic stabilizer Irganox 1010 (manufactured by BASF Chiba) as a heat stabilizer, and the mixture was kneaded using a Labo Plastomill mixer manufactured by Toyo Seiki Seisakusho Co., Ltd. at a resin temperature of 280°C and a screw rotation speed of 150 rpm to obtain Polymer 4. The amount of the structural units in Polymer 4 was the same as that of Polymer 4a. The melting point (Tm) of Polymer 4 was 201° C., and the intrinsic viscosity [η] (in decalin at 135° C.) was 1.0 dl / g. Other physical properties of Polymer 4 are shown in Table 1.

[0107] <Production Example 5: Production of Polymer 5> [Preparation of Polymer 5a] At room temperature and under a nitrogen stream, 425 mL of purified decane was placed in a SUS polymerization vessel equipped with a stirrer having an internal volume of 1 L, and the temperature was raised to 40°C. After reaching 40°C, 0.8 mL (0.4 mmol in terms of aluminum atoms) of a decane solution of triisobutylaluminum (TIBAL) (0.5 mmol / mL in terms of aluminum atoms) was charged, and then 0.0020 mmol of the decane slurry of the prepolymerization catalyst component of Synthesis Example 4-2 was charged in terms of zirconium atoms. 16.25 NmL of hydrogen was charged, and then a mixture of 231 mL of 4-methyl-1-pentene and 20.6 mL of Linearene 168 (Idemitsu Kosan, a mixture of 1-hexadecene and 1-octadecene) was continuously charged into the polymerization vessel at a constant rate over 2 hours. The start of the charge of the mixture was regarded as the start of polymerization, and the temperature was maintained at 45°C for 4.5 hours. One hour and two hours after the start of polymerization, 16.25 NmL of hydrogen was charged. 4.5 hours after the start of polymerization, the temperature was lowered to room temperature, the pressure was released, and the polymerization liquid containing a white solid was immediately filtered to obtain a solid substance. This solid substance was dried under reduced pressure at 80°C for 8 hours to obtain polymer 5a. The yield was 128 g. The content of structural units in polymer 5a was 97.0 mol% derived from 4-methyl-1-pentene, and the total content of structural units derived from α-olefins was 3.0 mol%. Polymer 5a had a melting point (Tm) of 203°C and an intrinsic viscosity [η] (in decalin at 135°C) of 5.3 dl / g.

[0108] [Production of Polymer 5] Polymer 5a (100 parts by mass), 2 parts by mass of maleic anhydride, 0.02 parts by mass of 2,5-dimethyl-2,5-bis(t-butylperoxy)hexyne-3 (Perhexyne 25B, manufactured by NOF Corporation) as an organic peroxide, and 0.02 phr of the phenolic stabilizer Irganox1010 (manufactured by BASF Chiba) as a heat stabilizer were blended, and the mixture was kneaded using a Labo Plastomill mixer manufactured by Toyo Seiki Seisakusho Co., Ltd. at a resin temperature of 280°C and a screw rotation speed of 150 rpm, thereby obtaining polymer 5. The amount of the structural units in polymer 5 was the same as that of polymer 5a. The melting point (Tm) of polymer 5 was 203°C, the intrinsic viscosity [η] (in decalin at 135°C) was 0.8 dl / g, and the amount of graft modification was 1.5 mass%. Other physical properties of polymer 5 are shown in Table 1.

[0109] <Production Example 6: Production of Polymer 6> Polymer 6 was obtained by carrying out the same production process as for Polymer 5, except that Polymer 4a was used instead of Polymer 5a. The amount of the structural unit in polymer 6 was the same as that of polymer 4a. The melting point (Tm) of polymer 6 was 201° C., the intrinsic viscosity [η] (in decalin at 135° C.) was 0.9 dl / g, and the amount of graft modification was 1.5 mass%. Other physical properties of polymer 6 are shown in Table 1.

[0110] <Production Example 7: Production of Polymer 7> [Preparation of polymer 7a] At room temperature and under a nitrogen stream, 425 mL of purified decane was placed in a SUS polymerization vessel equipped with a stirrer having an internal volume of 1 L, and the temperature was raised to 40°C. After reaching 40°C, 0.8 mL (0.4 mmol in terms of aluminum atoms) of a decane solution of triisobutylaluminum (TIBAL) (0.5 mmol / mL in terms of aluminum atoms) was charged, and then 0.00175 mmol of the decane slurry of the prepolymerization catalyst component of Synthesis Example 4-2 was charged in terms of zirconium atoms. 23.75 NmL of hydrogen was charged, and then a mixture of 232 mL of 4-methyl-1-pentene and 19.6 mL of Linearene 168 (Idemitsu Kosan, a mixture of 1-hexadecene and 1-octadecene) was continuously charged into the polymerization vessel at a constant rate over 2 hours. The start of the charge of the mixture was regarded as the start of polymerization, and the temperature was maintained at 45°C for 4.5 hours. 23.75 NmL of hydrogen was charged 1 hour and 2 hours after the start of polymerization. 4.5 hours after the start of polymerization, the temperature was lowered to room temperature, the pressure was released, and the polymerization liquid containing a white solid was immediately filtered to obtain a solid substance. This solid substance was dried at 80°C under reduced pressure for 8 hours to obtain polymer 7a. The yield was 146 g. The content of structural units in polymer 7a was 96.7 mol% derived from 4-methyl-1-pentene, and the total content of structural units derived from α-olefins was 3.3 mol%. Polymer 7a had a melting point (Tm) of 203°C and an intrinsic viscosity [η] (in decalin at 135°C) of 4.0 dl / g.

[0111] [Production of Polymer 7] Polymer 7 was obtained by carrying out the same production process as for Polymer 5, except that Polymer 7a was used instead of Polymer 5a. The amount of the structural units in polymer 7 was the same as that of polymer 7a. The melting point (Tm) of polymer 7 was 203° C., the intrinsic viscosity [η] (in decalin at 135° C.) was 0.9 dl / g, and the amount of graft modification was 1.6 mass%. Other physical properties of polymer 7 are shown in Table 1.

[0112] <Production Example 8: Production of Polymer 8> Polymer 8 was obtained by carrying out the same production process as for Polymer 5, except that Polymer 3 was used instead of Polymer 5a. The amount of the structural units in polymer 8 was the same as that in polymer 3. The melting point (Tm) of polymer 8 was 210° C., the intrinsic viscosity [η] (in decalin at 135° C.) was 0.8 dl / g, and the amount of graft modification was 1.5 mass%. Other physical properties of polymer 8 are shown in Table 1.

[0113] <Production Example 9: Production of Polymer 9> Polymer 9 was obtained by polymerizing monomers while changing the ratio of 4-methyl-1-pentene, 1-decene, and hydrogen in a manner similar to the polymerization methods described in Comparative Examples 7 and 9 of WO 2006 / 054613. The melting point (Tm) of the polymer was 233°C, and the intrinsic viscosity [η] (in decalin at 135°C) was 1.3 dl / g. Other physical properties of Polymer 9 are shown in Table 1.

[0114] <Production Example 10: Production of Polymer 10> A 1.5-liter stainless steel autoclave equipped with an agitator and thoroughly purged with nitrogen was charged with 750 ml of 4-methyl-1-pentene at 23° C. 0.75 ml of a 1.0 mmol / ml toluene solution of triisobutylaluminum (TIBAL) was charged into the autoclave, and the agitator was turned on. Next, the autoclave was heated to an internal temperature of 60°C, and pressurized with propylene so that the total pressure was 0.15MPa (gauge pressure). Then, 0.34ml of a toluene solution containing 1mmol of methylaluminoxane in terms of aluminum atom and 0.003mmol of diphenylmethylene (1-ethyl-3-t-butyl-cyclopentadienyl) (2,7-di-t-butyl-fluorenyl) zirconium dichloride, which had been prepared in advance, was pressed into the autoclave with nitrogen to start polymerization. During the polymerization reaction, the temperature was adjusted so that the internal temperature of the autoclave was 60°C. Five minutes after the start of polymerization, 5ml of methanol was pressed into the autoclave with nitrogen to stop the polymerization, and the autoclave was depressurized to atmospheric pressure. Acetone was poured into the reaction solution while stirring. The obtained powder-like polymer containing the solvent was dried at 130°C under reduced pressure for 12 hours. The obtained polymer 10 weighed 19.9 g, and had a 4-methyl-1-pentene content of 92.0 mol % and a propylene content of 8.0 mol % in the polymer 10. The melting point (Tm) of the polymer 10 was 180° C., and the intrinsic viscosity [η] was 1.6 dl / g.

[0115] [Table 1-1]

[0116] [Table 1-2]

[0117] <Preparation Example 2: Preparation of a coating agent by dissolving the composition (X1-1)> To 10 g of polymer 1 (i.e., the mass of polymer 1 is taken as 100% by mass), 0.1% by mass of tri(2,4-di-t-butylphenyl)phosphate as an antioxidant and 0.1% by mass of n-octadecyl-3-(4'-hydroxy-3',5'-di-t-butylphenyl)propionate as a heat stabilizer were added, and methylcyclohexane (manufactured by Wako Pure Chemical Industries, Ltd.) was added so that the solid content concentration became 5% by mass. The mixture was stirred at 200 rpm for 1 hour at 90°C to produce a coating agent in which a composition (X1-1) containing polymer 1 was dissolved.

[0118] <Preparation Example 3: Preparation of a coating agent by dissolving the composition (X1-2)> A coating agent was prepared in the same manner as in Preparation Example 2, except that Polymer 2 was used instead of Polymer 1.

[0119] <Preparation Example 4: Preparation of a coating agent by dissolving the composition (X1-3)> A coating agent was prepared in the same manner as in Preparation Example 2, except that Polymer 3 was used instead of Polymer 1.

[0120] <Preparation Example 5: Preparation of a coating agent by dissolving the composition (X1-4)> A coating agent was prepared in the same manner as in Preparation Example 2, except that Polymer 4 was used instead of Polymer 1.

[0121] <Preparation Example 6: Preparation of a coating agent by dissolving the composition (X2-1)> To 10 g of polymer 5 (i.e., the mass of polymer 5 is 100% by mass), 0.1% by mass of tri(2,4-di-t-butylphenyl)phosphate as an antioxidant and 0.1% by mass of n-octadecyl-3-(4'-hydroxy-3',5'-di-t-butylphenyl)propionate as a heat stabilizer were added, and methylcyclohexane (manufactured by Wako Pure Chemical Industries, Ltd.) was added so that the solid content concentration was 5% by mass, and the mixture was stirred at 200 rpm for 1 hour at 90°C. After cooling to 23°C, 0.01% by mass of Takenate D170N (manufactured by Mitsui Chemicals, Inc.) was added and stirred at 200 rpm for 5 minutes to produce a coating agent in which a composition (X2-1) containing polymer 5 was dissolved.

[0122] <Preparation Example 7: Preparation of a coating agent by dissolving the composition (X2-2)> A coating agent was prepared in the same manner as in Preparation Example 6, except that Polymer 6 was used instead of Polymer 5.

[0123] <Preparation Example 8: Preparation of a coating agent by dissolving the composition (X2-3)> A coating agent was prepared in the same manner as in Preparation Example 6, except that Polymer 7 was used instead of Polymer 5.

[0124] <Preparation Example 9: Preparation of a coating agent by dissolving the composition (X2-4)> A coating agent was prepared in the same manner as in Preparation Example 6, except that Polymer 8 was used instead of Polymer 5.

[0125] <Preparation Example 10: Preparation of a coating agent containing composition (X2-5) dissolved therein> To 10 g of polymer 5 (i.e., the mass of polymer 5 is taken as 100% by mass), 0.1% by mass of tri(2,4-di-t-butylphenyl)phosphate as an antioxidant and 0.1% by mass of n-octadecyl-3-(4'-hydroxy-3',5'-di-t-butylphenyl)propionate as a heat stabilizer were added, and methylcyclohexane (manufactured by Wako Pure Chemical Industries, Ltd.) was added so that the solid content concentration became 5% by mass. The mixture was stirred at 200 rpm for 1 hour at 90°C to produce a coating agent in which a composition (X2-5) containing polymer 1 was dissolved.

[0126] <Preparation Example 11: Preparation of a coating agent containing composition (X2-6) dissolved therein> A coating agent was prepared in the same manner as in Preparation Example 10, except that Polymer 6 was used instead of Polymer 5.

[0127] <Preparation Example 12: Preparation of a coating agent containing composition (X2-7) dissolved therein> A coating agent was prepared in the same manner as in Preparation Example 10, except that Polymer 7 was used instead of Polymer 5.

[0128] <Preparation Example 13: Preparation of a coating agent containing the composition (X2-8) dissolved therein> A coating agent was prepared in the same manner as in Preparation Example 10, except that Polymer 8 was used instead of Polymer 5.

[0129] <Preparation Example 14: Preparation of a coating agent containing a composition (CX1-1) dissolved therein> A coating agent was prepared in the same manner as in Preparation Example 2, except that Polymer 9 was used instead of Polymer 1. Although the mixture was stirred, most of Polymer 9 did not dissolve and remained undissolved. Therefore, a composition in which Polymer 9 was dissolved in a concentration sufficient for forming a coating film could not be obtained.

[0130] <Preparation Example 15: Preparation of a coating agent containing the composition (CX1-2) dissolved therein> A coating agent was prepared in the same manner as in Preparation Example 2, except that Polymer 10 was used instead of Polymer 1.

[0131] <Example 1> [Creation of laminate] The applicator settings were adjusted so that the thickness of the resin layer obtained after drying of composition (X2-1) would be 0.1 μm. The coating agent in which composition (X2-1) was dissolved was applied to a 50 mm square x 3 mm thick soda glass plate at 23°C, uniformly spread with an applicator, and then dried at 80°C for 60 seconds to produce a resin layer (II). Thereafter, a coating agent in which the composition (X1-1) was dissolved was applied onto the resin layer (II) so that the thickness of the resin layer was 0.1 μm, and the coating was uniformly spread with an applicator, followed by drying for 3 hours at 100° C. to prepare a resin layer (III) and obtain a laminate. Note that, in order to serve as a control in the heat resistance test described later, another laminate in which the resin layer (II) and the resin layer (III) were laminated was prepared by the same treatment.

[0132] [Transparency] The produced laminate was measured at 23°C using a haze meter NDH2000 (manufactured by Nippon Denshoku Industries Co., Ltd.) in accordance with JIS K 7136, and the haze values ​​obtained were used to evaluate the laminate according to the following criteria. The evaluation results are shown in Table 2-1. In the following description, Tables 2-1 to 2-3 are collectively referred to as Table 2. [Evaluation Criteria] A: Haze less than 1% B: Haze 1% or more

[0133] [Water repellency test] The laminate was placed horizontally at 23°C, water was dropped onto the resin layer (III) with a dropper, the laminate was turned perpendicular to the horizontal plane (inclined at 90°), and after 5 seconds, the traces of the water droplets were observed and evaluated according to the following criteria. The evaluation results are shown in Table 2. [Evaluation Criteria] A: No water droplets were observed visually on the surface of the resin layer (III). B: Water droplets were visually observed on the surface of the resin layer (III).

[0134] <Heat resistance> The prepared laminate was placed in an oven set at 180°C for 10 minutes with the resin layer (III) facing up, and then placed at 23°C for 10 minutes with the resin layer (III) facing up. The laminate prepared for control was not heated in the oven, so the appearance of the laminate that had been heat-treated in the oven was compared visually with the appearance of the control laminate, and evaluation was performed according to the following evaluation criteria. The evaluation results are shown in Table 2. [Evaluation Criteria] A: The appearance of the resin layer (III) of the heat-treated laminate was almost the same as that of the control laminate. B: Changes such as dissolution or cracks were observed in the resin layer (III) of the laminate that had been subjected to heat treatment.

[0135] <Residual adhesion rate> [Peel strength of adhesive tape after being attached to resin layer] A 25 mm wide adhesive tape (31B, manufactured by Nitto Denko Corporation) was lightly pressed onto the surface of the resin layer (III) of the laminate, and a 2 kg roller was rolled back and forth on it to attach it. After the adhesive tape was attached, it was left in a room at 23°C / 50%RH for 3 hours, and then peeled off by hand. The adhesive surface of the adhesive tape after peeling was lightly pressed onto a polyester film (Lumirror (registered trademark) S10 manufactured by Toray Industries, Inc.), and a 2 kg roller was rolled back and forth on it to attach (re-attach), and it was left in a room at 23°C / 50%RH for 3 hours. Thereafter, the 180° peel strength (crosshead speed 300 mm / min) of the adhesive tape attached to the polyester film was measured (apparatus: 201X type universal testing machine manufactured by Intesco).

[0136] [Peel strength of adhesive tape after being attached to a Teflon (registered trademark) plate] For comparison, a 25 mm wide adhesive tape was attached to the resin layer in the same manner as when the peel strength of the adhesive tape after attachment to the resin layer was measured, except that a Teflon plate was used instead of the above laminate, and the adhesive tape was reattached to the polyester film, and the peel strength of the adhesive tape after reattachment was measured.

[0137] [Calculation of residual adhesion rate] The residual adhesion rate was calculated from the following formula: In the following formula, ADlam is the peel strength of an adhesive tape when it is attached to a polyester film after being peeled off from a resin layer of a laminate, and ADt is the peel strength of an adhesive tape when it is attached to a polyester film after being peeled off from a Teflon plate. Residual adhesion rate (%)=ADlam / ADt×100

[0138] The residual adhesion rate was evaluated according to the following evaluation criteria. The results are shown in Table 2. Table 2 also shows the type of composition contained in the resin layer of the laminate used in the evaluation. [Evaluation Criteria] A:Residual adhesion rate 80% or more B: Residual adhesion rate less than 80%

[0139] <Examples 2 to 7> In the laminate examples, except that the coating agent used was changed so that the resin layer (II) and the resin layer (III) were as shown in Table 2, a laminate was obtained in the same manner as in Example 1, and evaluated in the same manner as in Example 1. The evaluation results are shown in Table 2.

[0140] <Example 8> [Creation of laminate] The applicator settings were adjusted so that the thickness of the resin layer obtained after drying of composition (X5) was 0.1 μm, and the coating agent in which composition (X5) was dissolved was applied to a 50 mm square x 3 mm thick soda glass plate at 23°C and uniformly spread with an applicator, and then dried at 100°C for 3 hours to produce a resin layer (II) and obtain a laminate. The obtained laminate was evaluated in the same manner as in Example 1, except that in the water repellency test, water was dropped from a dropper onto the resin layer (II) instead of the resin layer (III), in the heat resistance test, the resin layer (II) was placed on top instead of the resin layer (III) when left to stand in an oven and at a temperature of 23°C, and in the residual adhesion test, the adhesive tape was attached onto the resin layer (II) instead of the resin layer (III). The evaluation results are shown in Table 2.

[0141] <Examples 9 to 19, Comparative Examples 3 and 4> In the laminate examples, a laminate was obtained in the same manner as in Example 8, except that the coating agent used was changed so that the resin layer (II) would be as shown in Table 2, and evaluated in the same manner as in Example 8. The evaluation results are shown in Table 2. In Comparative Example 3, the polymer 9 was not dissolved in the coating agent (CX1-1) at a concentration sufficient for forming a coating film, so that a laminate could not be obtained.

[0142] <Comparative Example 1> Using uncoated 50 mm square × 3 mm thick soda glass, evaluation was carried out in the same manner as in Example 1. The results obtained are shown in Table 2.

[0143] <Comparative Example 2> Polymer 9 was molded into a film at a cylinder temperature of 280°C using a cast film molding machine with a T die to obtain a cast film having a thickness of 30 μm. The obtained cast film was cut into 40 × 40 mm and placed on a 50 mm square × 3 mm thick soda glass plate. The cast film was melt-bonded by heating in a 240°C oven for 30 minutes to prepare a resin layer (II) and obtain a laminate, which was evaluated in the same manner as in Example 8. The obtained results are shown in Table 2.

[0144] <Comparative Example 5> 100 parts by mass of silicone release agent (KS-847H, manufactured by Shin-Etsu Chemical Co., Ltd.) and 3.3 parts by mass of silicone curing catalyst (CAT-PL-50T, manufactured by Shin-Etsu Chemical Co., Ltd.) were added, and diluted to 0.3% by weight with a mixed solvent consisting of toluene (manufactured by Idemitsu Petrochemical Co., Ltd.), hexane (normal hexane, manufactured by Maruzen Petrochemical Co., Ltd.), and methyl ethyl ketone (MEK, manufactured by Idemitsu Kosan Co., Ltd.) in a weight ratio of 1:2:1 to obtain a coating agent (CX-3). A laminate was obtained in the same manner as in Example 8, except that the coating agent used was changed, and was evaluated in the same manner as in Example 8. The evaluation results are shown in Table 2.

[0145] [Table 2-1]

[0146] [Table 2-2]

[0147] [Table 2-3]

Claims

1. A substrate layer (I) having a surface comprising glass; a resin layer (II) having a thickness of 10 μm or less, which is formed from a composition (X) containing a 4-methyl-1-pentene polymer (A) satisfying the following requirement (a) and is in contact with the surface; A laminate having the following structure: (a) The melting point (Tm) measured by a differential scanning calorimeter (DSC) is greater than 180° C. and less than or equal to 220° C.

2. The laminate according to claim 1, wherein the 4-methyl-1-pentene polymer (A) further satisfies the following requirement (b): (b) The endothermic end temperature (TmE) in the melting (endothermic) curve measured by DSC is 230° C. or lower.

3. The laminate according to claim 1 or 2, wherein the 4-methyl-1-pentene polymer (A) further satisfies the following requirement (c): (c) The heat generation onset temperature (TcS) in the crystallization (heat generation) curve measured by DSC is 210° C. or lower.

4. The laminate according to claim 1 or 2, wherein the 4-methyl-1-pentene polymer (A) further satisfies the following requirement (f): (f) The crystallization temperature (Tc) in the crystallization (exothermic) curve measured by DSC is 110 to 200°C.

5. 3. The laminate according to claim 1, wherein the 4-methyl-1-pentene polymer (A) has an intrinsic viscosity [η] measured in decalin at 135° C. in the range of 0.5 to 6.0 dl / g.

6. 3. The laminate according to claim 1, wherein the amount (U1) of structural units derived from 4-methyl-1-pentene in the 4-methyl-1-pentene polymer (A) is 84.0 to 100.0 mol %, and the total amount (U2) of structural units derived from ethylene or an α-olefin having 3 to 20 carbon atoms (excluding 4-methyl-1-pentene) is 16.0 to 0.0 mol % (the sum of U1 and U2 is 100 mol %).

7. The 4-methyl-1-pentene polymer (A) is a graft-modified 4-methyl-1-pentene polymer (A2), 3. The laminate according to claim 1, wherein the graft-modified amount of the modified 4-methyl-1-pentene polymer (A2) is 0.1 to 5.0% by mass.

8. The laminate according to claim 7 , wherein the composition (X) further comprises an isocyanate compound (B).

9. The substrate layer (I), The resin layer (II), A resin layer (III) having a thickness of 10 μm or less, which is formed from a composition (X1) containing an unmodified 4-methyl-1-pentene polymer (A1), which is a 4-methyl-1-pentene polymer (A) that has not been graft-modified; The laminate according to claim 7 , comprising, in this order:

10. An article comprising the laminate of claim 1 or 2.

Citation Information

Patent Citations

  • Water repellant for glass

    JP2009137775A

  • Coating composition

    JP2016169307A